Child and adolescent sexual violence in the Costa Rican press (2014-2015) - Ramírez Roldán, José David (2020)
This paper explores the discursive productions issued by the newspaper La Nación about the factors linked to sexual violence during childhood and adolescence, from January 1, 2014 to April 23, 2015. From these perspectives issued by the media written communication poses its position as part of a system of representations that circulate in civil society, starting in some phenomena can be made a systematic elaboration of the contents and reconstructed statistical evidence with a relevant validity of cases for the national sphere.